2002
DOI: 10.1007/s127-002-8209-5
|View full text |Cite
|
Sign up to set email alerts
|

Health and well-being among 70-year-old migrants living in Sweden - results from the H 70 gerontological and geriatric population studies in Göteborg

Abstract: The results indicate poorer subjective health in older migrants than natives in Göteborg, and also point to a "healthy migrant" effect on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
45
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 26 publications
10
45
0
Order By: Relevance
“…However, to control the effect of the age, analyses of covariance were carried out. One main result of our study was a significantly worse self-reported mental as well as physical HRQoL found in the Polish immigrants as compared to the German norm population, a result consistent with previous studies on HRQoL demonstrating better outcome for the indigenous population compared to both Polish immigrants (Silveira et al, 2002) as well as other immigrant groups (Koochek, Montazeri, Johansson, & Sundquist, 2007). A lower mental as well as physical HRQoL in Polish immigrants in relation to the German norm population may in part be explained depending on different immigration stress theories: Immigration may be associated with various stressors and losses and may be regarded to be a critical life event or even a trauma (Grinberg & Grinberg, 1990) evoking mental illness or a tendency to somatize (Masumbuku, 1995).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…However, to control the effect of the age, analyses of covariance were carried out. One main result of our study was a significantly worse self-reported mental as well as physical HRQoL found in the Polish immigrants as compared to the German norm population, a result consistent with previous studies on HRQoL demonstrating better outcome for the indigenous population compared to both Polish immigrants (Silveira et al, 2002) as well as other immigrant groups (Koochek, Montazeri, Johansson, & Sundquist, 2007). A lower mental as well as physical HRQoL in Polish immigrants in relation to the German norm population may in part be explained depending on different immigration stress theories: Immigration may be associated with various stressors and losses and may be regarded to be a critical life event or even a trauma (Grinberg & Grinberg, 1990) evoking mental illness or a tendency to somatize (Masumbuku, 1995).…”
supporting
confidence: 91%
“…Many of these studies have been conducted in Sweden. For example, a study in Sweden on the health and well-being of older immigrant groups (Eastern and Western Europeans, Nordic immigrants, Mediterraneans and non-Europeans) compared to the native Swedish population demonstrated a poorer subjective health for the immigrants, non-Nordic immigrants (including Polish immigrants) reporting significantly lower mean scores in all SF-36 health domains than the Swedes (Silveira, Skoog, Sundh, Allebeck, & Stehen, 2002). The reasons for immigration and legal conditions of Polish immigrants in Germany and in Sweden differ.…”
Section: Findings On Mental Health Of Immigrantsmentioning
confidence: 99%
“…Anxiety, depression and an increased risk for psychotic disorders have been reported to be prevalent in some migrant populations (Odegaard 1932;Coid et al 2008;Silveira et al 2002;Aichberger et al 2010;Bhugra 2004). These findings are explained, at least to some extent, in terms of higher social adversity, migrant stress, social isolation, depression, loneliness and poor living conditions of the migrant populations.…”
Section: Psychic Costs Of (Return) Migrationmentioning
confidence: 98%
“…A Swedish study showed differences between migrants and native citizens aged 70 years in self-reported chronic health issues, migrants suffering more often of some specific chronic symptoms such as poor vision, urinary difficulties and dizziness. 21 A Swiss survey of the migrant population health in 2007 showed variations of self-reported health between different subgroups, particularly according to the country of origin, the legal status or the socio-economic level. 13,22 Finally, undocumented immigrants may forgo healthcare for economical reasons or fear of notification of their stay to the police, 6 even though there is possibility to subscribe a health insurance without being reported to the immigration administration.…”
Section: Discussionmentioning
confidence: 99%